Ovariectomized mice and postmenopausal women exhibit analogous loss of genital epithelial integrity. Issue 2 (3rd April 2021) - Quispe Calla, Nirk E.; Vicetti Miguel, Rodolfo D.; Aceves, Kristen M.; Huang, Huijie; Howitt, Brooke; Cherpes, Thomas L.
ABSTRACT: Roughly half of all postmenopausal women are affected by the genitourinary syndrome of menopause (GSM). Symptoms of GSM, including vaginal irritation and dyspareunia, occur as reduced estrogen (E) production elicits loss of elasticity and other changes in genital tract tissue. While the use of the injectable contraceptive depot-medroxyprogesterone acetate (DMPA) likewise lowers serum E concentrations in reproductive age women and is associated with decreased genital levels of the cell-cell adhesion molecules desmoglein-1 (DSG1) and desmocollin-1 (DSC1) and impaired genital epithelial barrier function, the relevance of these findings to women in menopause is uncertain. Exploring the impact of menopause on genital epithelial integrity herein, we detected significantly lower levels of DSG1 and DSC1 in ectocervical tissue from menopausal and postmenopausal vs premenopausal women. Using ovariectomized (OVX) mice as a menopause model, we comparably saw significantly lower vaginal tissue levels of DSG1 and DSC1 in OVX mice vs. mice in estrus. Compared to estrus-stage mice and E-treated OVX mice, DMPA-treated ovary-intact mice and OVX mice also exhibited significantly reduced genital epithelial barrier function, greater susceptibility to genital herpes simplex virus type 2 infection, and delayed clearance of genital Chlamydia trachomatis infection. Current studies thus identify analogous loss of genital epithelial integrity in OVX mice and menopausal and postmenopausal women. By showing that loss of genital epithelial integrity is associated with increased mouse susceptibility to bacterial and viral pathogens, our findings also prioritize the need to resolve if reduced genital epithelial integrity in postmenopausal women is a significant risk factor for genital infection.